Clofazimine: an old drug for never-ending diseases - Riccardi, Niccolò; Giacomelli, Andrea; Canetti, Diana; Comelli, Agnese; Intini, Enrica; Gaiera, Giovanni; Diaw, Mama M; Udwadia, Zarir; Besozzi, Giorgio; Codecasa, Luigi; Biagio, Antonio Di (Future microbiology, 2020)
Clofazimine (CFZ), an old hydrophobic riminophenazine, has a wide range of antimycobacterial activity ranging from leprosy to nontuberculous mycobacterial diseases. CFZ has several advantages such as a favorable pharmacokinetic profile, dose-dependent side effects as well as low price. In this narrative review, we have assessed the clinical development of CFZ, starting from the potential mechanism of actions, to the spectrum of side effects and potential drug–drug interactions, highlighting its current place in therapy and future possible use in leprosy, nontuberculous mycobacterial diseases and drug-resistant tuberculosis.